MANFAAT AVERRHOA CARAMBOLA DALAM MENURUNKAN HIPERTENSI - Jenita Doli Tine Donsu (FORIKES, 2018)
MANFAAT AVERRHOA CARAMBOLA DALAM MENURUNKAN HIPERTENSI Jenita Doli Tine Donsu*), Harmilah**), Maria H. Bakri***) *) **)***)Health Polytechnic of Health Ministry Yogyakarta Jl. Tata Bumi No. 03 Banyuraden, Gamping, Sleman, Yogyakarta Email: donsu.tine@gmail.com ABSTRACT Hypertension is a common health problem in the community. Uncontrolled hypertension can lead to degenerative diseases, such as congestive heart failure, kidney failure, and vascular disease. Hypertension is called the